AN EVALUATION OF THE DENTAL FEATURES USED TO DISTINGUISH TYPOTHERIOPSIS FROM PSEUDOTYPOTHERIUM (MESOTHERIIDAE, NOTOUNGULATA): REAPPRAISALS AND PROPOSALS REGARDING THEIR SYSTEMATIC VALUE (Ameghiniana, 2018)
The Mesotheriinae records in the late Neogene of Argentina are mostly grouped in two genera: Typotheriopsis and Pseudotypotherium. Both taxa were poorly diagnosed and/or based on juvenile specimens. Traditionally, the dental feature considered to distinguish them is the presence of a lingual groove in the last upper premolar. Other features were mostly dismissed or considered non-informative at a generic level. Based on this, we reanalyzed dental features in Typotheriopsis and Pseudotypotherium samples to evaluate their relevance in a taxonomic framework. This study brings new qualitative and quantitative tools to appraise diagnostic features present in fossil fragments and isolated dental mesotheriine pieces.